Gender intentional approaches to enhance health social enterprises in Africa: a qualitative study of constraints and strategies - Kevin McKague; Sarah Harrison; Jenipher Musoke (BMC, 2021)
Abstract Background Health social enterprises are experimenting with community health worker (CHW) models that allow for various income-generating opportunities to motivate and incentivize CHWs. Although evidence shows that improving gender equality contributes to the achievement of health outcomes, gender-based constraints faced by CHWs working with social enterprises in Africa have not yet been empirically studied. This study is the first of its kind to address this important gap in knowledge. Methods We conducted 36 key informant interviews and 21 focus group discussions between 2016 and 2019 (for a total of 175 individuals: 106 women and 69 men) with four health social enterprises in Uganda and Kenya and other related key stakeholders and domain experts. Interview and focus group transcripts were coded according to gender-based constraints and strategies for enhanced performance as well as key sites for intervention. Results We found that CHW programs can be more gender responsive. We introduce the Gender Integration Continuum for Health Social Enterprises as a tool that can help guide gender equality efforts. Data revealed female CHWs face seven unique gender-based constraints (compared to male CHWs): 1) higher time burden and lack of economic empowerment; 2) risks to personal safety; 3) lack of career advancement and leadership opportunities; 4) lack of access to needed equipment, medicines and transport; 5) lack of access to capital; 6) lack of access to social support and networking opportunities; and 7) insufficient financial and non-financial incentives. Data also revealed four key areas of intervention: 1) the health social enterprise; 2) the CHW; 3) the CHW's partner; and 4) the CHW's patients. In each of the four areas, gender responsive strategies were identified to overcome constraints and contribute to improved gender equality and community health outcomes. Conclusions This is the first study of its kind to identify the key gender-based constraints and gender responsive strategies for health social enterprises in Africa using CHWs. Findings can assist organizations working with CHWs in Africa (social enterprises, governments or non-governmental organizations) to develop gender responsive strategies that increase the gender and health outcomes while improving gender equality for CHWs, their families, and their communities.